KONTIBUSI MOTIVASI DAN KESIAPAN PRAKTEK KERJA INDUSTRI TERHADAP PRESTASI PRAKTEK KERJA INDUSTRI - Ahmad Arif Daulay; Hanesman Hanesman Hanesman (Universitas Negeri Padang, 2019)
This study aims to determine the Contribution of Motivation and Readiness of Industrial Internship Practices to Industrial Job Training Achievement of Class XI Students in Audio Video Engineering Skills Program at SMK Negeri 1 West Sumatra. The population of this study was all students of class XI audio video engineering expertise program at SMK Negeri 1 West Sumatra 2018/2019 academic year totaling 31 students. data retrieval uses a type of saturated sample, sampling 31 students. Data collection methods in the study used documentation and questionnaires that were shared with students. This data analysis technique uses multiple regression analysis. The results showed that (1) contributing to the Motivation and Readiness of Industrial Internships together contributed 45.15% to the industrial work practice achievement, (2) motivation giving a contribution of 34.69% of the industrial work practice achievements, (3) the readiness of industrial work practices together contributed 21.62% to the achievement of industrial work practices. So, it can be concluded that the Motivation and Readiness of Industrial Work Practices Contribute to the Achievements of Industry. Keywords: Motivation,industry practicereadiness,industrial work practice achievements.